PENGARUH UKURAN PERUSAHAAN DAN KOMITE AUDIT TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2012 – 2014 - Dewi Saptantinah Puji Astuti, Esther Irene Nainggolan, Rispantyo & (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2016)
The purpose of this research was: 1) analyzes the significance of the influence of the size of the company management against earnings on manufactured companies consumer goods industry listed on The Indonesia Stock Exchange. 2) analyzes the significance of the audit committeeof the company management against earnings on manufactured companies consumer goods industry listed of The Indonesia Stock Exchange. Research methods method using case studies. The data type of the data being used is qualitative and quantitative data. The source data used the data of second. Method of collection used documentation. Technique of data analysis of this research was multiple regressions. The research results obtained conclusions: 1) the size of the company and significant negative effect on eranings managementon manufactured companies consumer goods industry listed on The Indonesia Stock Exchange. 2) the audit committee has a significant effect on eranings management on manufactured companies consumer goods industry listed of The Indonesia Stock Exchange.Keywords: the size of the company, the audit committee, earnings management.